Розрахунки повзучості при неперервному зростанні температури - Бреславський, Дмитро Васильович; Пащенко, Сергій Олександрович; Татарінова, Оксана Андріївна (НТУ "ХПІ", 2015)
В статті надано математичну постановку трьохвимірних задач повзучості та нестаціонарної теплопровідності. Як метод розв’язання використано метод скінченних елементів. Описано розроблені алгоритми, які є основою створеного програмного забезпечення. Отримано константи до рівняння стану повзучості бронзи у широкому діапазоні температур. Проведено одночасний розв’язок сформульованих задач на прикладі нагрівання бронзового стрижня та визначено достовірність роботи розробленого програмного забезпечення.

The mathematical statements of creep and transient heat transfer three dimensional problems are presented in a paper. Finite Element Method is used for solution of boundary problems as well as time step integration method for initial ones. The algorithms which are the foundations of developed software are discussed. The values of constants, which are included in state equations for wide range of temperatures, are obtained. The simultaneous solutions of analyzed problems have been performed by use of example of heating the bronze bar in tension. The time dependencies of temperature and creep strain were obtained by numerical way. The correctness of developed software was estimated.
Creep calculations at steady growth of temperature
Keywords: рівняння стану; теплопровідність; метод скінченних елементів; бронзовий стрижень; state equation; creep curves; transient heat transfer; Finite Element Method; bronze bar